(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: The aim of this study was to estimate the frequency of inflammatory, benign and malignant lesions in prostatic biopsies. Study Design: Descriptive study. Place and Duration: The study was carried out at the department of Histopathology at PGMI Lahore from January 2009 to January 2011. Materials and Methods: 220 prostatic biopsies (radical prostatectomy, TURP and core biopsies) received from Urology department of Lahore General Hospital were included in this study. Results: A total of 220 prostatic specimens were included in this study. Out of these 62% were reported as benign, 4% as premalignant and 33% as malignant neoplasms.